The leukocyte esterase test for periprosthetic joint infection is not affected by prior antibiotic administration - Shahi, A; Alvand, A; Ghanem, E; Restrepo, C; Parvizi, J (Journal of Bone and Joint Surgery, 2019)
BACKGROUND: It has been demonstrated that administration of antibiotics prior to performing diagnostic testing for periprosthetic joint infection can interfere with the accuracy of the standard diagnostic tests. Therefore, the purpose of this study was to evaluate the effects of antibiotic administration prior to performing the synovial leukocyte esterase strip test for periprosthetic joint infection. METHODS: We identified 121 patients who underwent revision hip or knee arthroplasty for a Musculoskeletal Infection Society (MSIS)-confirmed periprosthetic joint infection. All patients also had a leukocyte esterase strip test performed. Patients in one group (32%) took antibiotics prior to the diagnostic workup, whereas patients in another group (68%) did not receive antibiotics within 2 weeks of the diagnostic workup. The leukocyte esterase strip test, erythrocyte sedimentation rate (ESR), serum C-reactive protein (CRP), synovial white blood-cell (WBC) count, and polymorphonuclear neutrophil (PMN) percentage were collected and were compared between the 2 groups. RESULTS: The median serum ESR (85 compared with 67 mm/hr for patients who did not and did receive antibiotics; p = 0.009), CRP (16.5 compared with 12.9 mg/L; p = 0.032), synovial WBC count (45,675 compared with 9,650 cells/µL; p < 0.0001), and PMN percentage (93% compared with 88%; p = 0.004) were all significantly lower for patients receiving antibiotics. Furthermore, the administration of antibiotics resulted in a significant decrease in the sensitivity of all tests, except leukocyte esterase: ESR (79.5% in the antibiotics cohort compared with 92.7% in the no-antibiotics cohort [relative risk (RR) for false-negative results, 2.8; p = 0.04]), CRP (64.2% compared with 81.8% [RR, 1.9; p = 0.03]), WBC count (69.3% compared with 93.4% [RR, 5.0; p = 0.001]), PMN percentage (74.4% compared with 91.5% [RR, 3.0; p = 0.01]), and leukocyte esterase (78% compared with 83% [RR, 1.6; p = 0.17]). The rate of negative cultures was higher in the antibiotics group at 30.7% compared with the no-antibiotics group at 12.1% (p = 0.015). CONCLUSIONS: This current study and previous studies have demonstrated that the administration of premature antibiotics can compromise the results of standard diagnostic tests for periprosthetic joint infection, causing significant increases in false-negative results. However, in this study, the leukocyte esterase strip test maintained its performance even in the setting of antibiotic administration. Antibiotic administration prior to diagnostic workups for periprosthetic joint infection stands to interfere with diagnosis. The leukocyte esterase strip test can be used as a reliable diagnostic marker for diagnosing periprosthetic joint infection even when prior antibiotics are administered. LEVEL OF EVIDENCE: Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence.